ANALISA EFEKTIFAS BLOWDOWN RATE DAN BLOWDOWN TIME PADA BOILER KAPASITAS 20 TON/JAM - Effendi, Zulham; Aisyah, Siti; Lubis, Muhammad Fauzan Ansyaqory (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2023)
Boiler blowdown is the removal of a portion of the water in a steam boiler which has a high TDS concentration and replacing it with new boiler feed water so that it will reduce the concentration of suspended or dissolved solid water from the boiler. The working system in the boiler is that heat is channeled to boiler water which will then form steam. Water has an important role in the boiler, if the water used is not according to standards it will cause problems such as scale, corrosion, deposits, carry over and other specific problems. In general, the water fed to the boiler contains a high content of TDS and other dissolved and insoluble solids in it. From this research it is known that during April, May and June the highest blowdown rate occurred on April 12, 2022, namely 2183.76 kg/hour and for the lowest blowdown rate occurred on June 7, 2022, namely 684.91 kg/hour. The highest blowdown time occurred on 12 April 2022, which was 0.74 minutes/hour or equivalent to 44.4 seconds, and the lowest blowdown time occurred on 07 June 2022, namely 0.23 minutes/hour or equivalent to 13.8 second. The high TDS value can affect the blowdown rate, blowdown time and blowdown percentage which will have an impact on the effectiveness of the blowdown rate, blowdown time and blowdown percentage in the boiler itself.